Social variation in size at birth and preterm delivery in the Czech Republic and Sweden, 1989-91 - Koupilová, I; Vågerö, D; Leon, D A; Pikhart, H; Príkazský, V; Holcík, J; Bobák, M (Paediatric and perinatal epidemiology, 1998)
All livebirths resulting from singleton pregnancies reported to the Czech (n = 380,633) and Swedish (n = 351,775) birth registries in 1989-91 were studied with respect to social variation in birthweight, ponderal index (weight/length at birth3) and preterm delivery. The mean birthweight was significantly lower in the Czech population (3310 g vs. 3522 g, P < 0.001). The mean difference in birthweight between children of mothers with primary and university education was 197 g [95% CI 190, 205] in the Czech and 136 g [95% CI 128, 144] in the Swedish population, adjusted for maternal age, parity and sex of the infant. Mean birthweight was significantly higher in mothers who were married or lived with partners in both countries; the difference was 167 g [95% CI 161, 173] in the Czech Republic (CR) and 86 g [95% CI 78, 94] in Sweden, adjusted for age, parity and sex. The extent of social variation in ponderal index and frequency of preterm birth was also greater in the CR. Between 1989 and 1991, mean birthweight in the CR fell from 3323 g to 3292 g (P < 0.001) and the social differences increased, largely as a result of more rapid worsening in the lower socio-economic groups. There did not appear to be such a decline in birthweight in Sweden. We suggest that the fall in mean birthweight and the increasing social variation in birth outcome in the CR is related to decline and divergence in living standards in 1989-91.
Keywords: lineární modely; Registries; novorozenec; Infant, Newborn; Švédsko; logistické modely; Infant, Premature; výsledek těhotenství; Pregnancy; Humans; novorozenec s nízkou porodní hmotností; lidé středního věku; dítě; registrace; Sweden; socioekonomické faktory; Child; porodní hmotnost; tělesná výška; Female; dospělí; Pregnancy Outcome; lidé; Socioeconomic Factors; Infant, Low Birth Weight; Adult; ženské pohlaví; Male; Middle Aged; Body Height; Birth Weight; Adolescent; Linear Models; těhotenství; Czech Republic; Česká republika; mužské pohlaví; novorozenec nedonošený; Logistic Models; mladiství